Knowledge Resources, ICT, and Their Links With SME Performance: The Role of Absorptive Capacity - Sulistyo, Heru (KnE Social Sciences, 2022)
In the industrial revolution 4.0, firms and SMEs are required to have dynamic capabilities to respond to environmental changes and increasing competitive pressures. Reconfiguring ICT and knowledge resources and capabilities is a must for firms in order to achieve performance and competitive advantages. This study aimed to bridge the research gap between knowledge resources and performance with absorptive capacity as an intervening variable. Moreover, this study also examined the effect of knowledge resources and ICT on absorptive capacity and performance. This study collected primary data from SMEs in Jepara, Rembang, and Semarang, Indonesia, through questionnaires, in-depth interviews, and focus group discussions. 285 SME owners participated. The data were analyzed employing SEM with multiple regression, which revealed that ICT significantly affected absorptive capacity and SME performance. Knowledge resources had a significant effect on absorptive capacity and SME performance. Furthermore, absorptive capacity had a significant effect on SMEs performance. Keywords: knowledge resource, ICT, dynamic capability, performance, SMEs